STATIONARY DYNAMIC RESPONSE OF A CIRCULAR RIGID FOUNDATION PARTIALLY SUPPORTED BY A FLEXIBLE PILE AND INTERACTING WITH A TRANSVERSELY ISOTROPIC SOIL - Lima, Luis Filipe do Vale; Labaki, Josue; Mesquita, Euclides (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper investigates the vertical response of rigid circular foundation resting on the surface of a three-dimensional, transversely isotropic soil. The foundation interacts with the soil by two mechanisms. First, the foundation is partially supported by a flexible pile embedded in soil, in which case there are no stresses at the soil-foundation interface. In the second mechanism, the foundation is partially supported by the soil through soil-foundation interface stress. This article studies the change in the foundation dynamic response when supported by these two distinct mechanisms. The present analysis is based on two previously solved problems, namely the interaction of a rigid foundation with a transversely isotropic soil (Labaki, Mesquita and Rajapakse, 2014) and the response of a flexible pile embedded in the transversely isotropic soil (Labaki, Mesquita and Rajapakse, 2015). The solutions to these two problems are computationally very demanding. The numerical studies reported in this article investigate the role of the mass-to-pile inertia ratio as well as the relative stiffness of the soil and the pile. An external vertical force acting on the foundation is considered as the excitation mechanism. The results are expressed in terms of vertical displacements of the foundation for distinct sets of parameters.